Pictând cu trupul - Dan, Marcela Livia (Symbolon, 2025)
Painting With the Body Ballet has been around since the 14th or 15th century and has influenced many artists. A unique person who changed the classical paradigm of ballet is Shahar Binyamini. He managed to revolutionize dance and break from the rigid norms created over the centuries, reaching amazing forms of bodily expression. He danced in the Batsheva dance company from 2006 to 2013, where he performed extensively in the repertoire of choreographers Ohad Naharin and Sharon Eyal. There, he developed a unique style that combines contemporary dance techniques with a deep exploration of human expression. Throughout his career, he has worked with some of the most influential names in contemporary dance, enriching his own choreographic vocabulary. After leaving the Batsheva dance company, Shahar began his international choreographic journey. Shahar Binyamini's choreography continues to challenge and expand the boundaries of contemporary dance, establishing him as a key figure of the global artistic scene.